„Śmierć Romka” (poznański Czerwiec w prozie Janusza Krasińskiego) - Urbanowski, Maciej (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The article reconstructs and analyses the image of Poznań 1956 protests in the well known novel cycle by Janusz Krasiński. For the protagonist, Szymon Bolesta, the death of Romek Strzałkowski is particularly painful, an event extensively reconstructed in the conclusion of Niemoc , one of the novels. The execution of Romek and the propaganda lies about it, are for Bolesta the key examples of the criminal nature of the communist regime, and the Black Thursday he interprets as an unsuccessful national uprising.